The Experience of marketing researches in the study of Japanese at Japanese department - Бaхaутдиновa, Г. (Journal of Oriental Studies, 2017)
This article assesses study the language at the Japanese department at university level. First it looks at the main reasons for decline in a number students who study the language at the Japanese department at university level. Second, the article analyses various tools used by foreign universities to improve teaching skills in learning Japanese language. Third the articles analyses various marketing tools used to attract new students on the example and experience of foreign universities.